Catalytic Oxidation of N-Phosphonomethyliminodiacetic Acid to Synthesize N-Phosphonomethylylycine - Xu1, Yufang; Dai1, Shujuan; Chen2, Tianyun (Asian Journal of Chemistry, 2013)
A process of preparing the herbicide N-phosphonomethylylycine by oxidizing N-phosphonomethyliminodiacetic acid was investigated. The content of N-phosphonomethylylycine was above 75.04 %. The solid yield was 73.34 % and the total yield was 87.63 % when the reaction was carried out with the mol ratio of the manganese salt catalyst and N-phosphonomethyliminodiacetic acid as 0.04:1 at 80 ºC under 0.4 MPa for 90 min.